Pengembangan Electronic Customer Relationship Management (E-CRM) Pada Toko Sepatu Aneka Sport Malang Dengan Metode Kerangka Kerja Dynamic CRM - Ghaniyu Zulfata; Niken Hendrakusma Wardani; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The business competition growing rapidly and the development of information technology are the reason for the company to change the company's thinking on business, which was once oriented towards profitability toward potential factors such as customer satisfaction. This can motivate companies to take advantage of technology in maintaining good relationships with customers in order to form customer loyalty. This study aims to design and build Electronic Customer Relationship Management (E-CRM) software in Aneka Sport shoe shop Malang by using framework dynamic of CRM method. The framewok dynamic dynamic of CRM method is used to analyze system requirements based on information obtained from customers, for customers and by customers. In this software implementation using waterfall system development method and built based website with PHP programming language and MySql database. The software is tested using white-box testing indicating that 3 functions can run correctly, black-box testing shows 23 valid status functions, compatibility tests that show the system works well on 8 types of website browser, and user acceptance testing shows 81.9% of users agree. From the test results can be concluded that this software has been successfully developed according to the design and can be accepted by the user.